The Essentiality of Motivation on Librarians Productivity in Nigerian Public Universities - Yaya, Japheth Abdulazeez (Asian Journal of Contemporary Education, 2021)
The study examined the essentiality of motivation in enhancing the effectiveness of librarians in Nigerian public universities. It adopted correlation survey research design. Its population consisted of 1,254 librarians in public university libraries in Nigeria, from which 923 were selected using simple random sampling. The research instrument used was a self-developed questionnaire. The study revealed that motivation is necessary in enhancing job performance of librarians in public university libraries in Nigeria. It concluded that contrary to general belief, motivation level of librarians in university libraries was high. It was recommended that university library management should continue to promote values such as improved employee recognition, good leadership style and improved employees’ motivational programmes that would increase productivity of its workforce.